Hemodynamic impingement and the initiation of intracranial side-wall aneurysms. Issue 3 (June 2018) - Riccardello, Gerald J; Changa, Abhinav R; Al-Mufti, Fawaz; Singh, I Paul; Gandhi, Chirag; Roman, Max; Prestigiacomo, Charles J
Objective: The natural history intracranial aneurysms (IA) remains poorly understood despite significant morbidity and mortality associated with IA rupture. Hemodynamic impingement resulting in elevations in wall shear stress and wall shear stress gradient (WSSG) has been shown to induce aneurysmal remodeling at arterial bifurcations. We investigate the hemodynamic environment specific to side-wall pre-aneurysmal vasculature. We hypothesize that fluid impingement and secondary flow patterns play a role in side-wall aneurysm initiation. Methods: Eight side-wall internal carotid artery aneurysms from the Aneurisk repository were identified. Pre-aneurysmal vasculature was algorithmically reconstructed. Blood flow was simulated with computational fluid dynamic simulations. An indicator of isolated fluid impingement energy was developed by insetting the vessel surface and calculating the impinging component of the fluid dynamic pressure. Results: Isolated fluid impingement was found to be elevated in the area of aneurysm initiation in 8/8 cases. The underlying fluid flow for each area of initiation was found to harbor secondary flow patterns known as Dean's vortices, the result of changes in momentum imparted by bends in the internal carotid artery (ICA). Conclusion: Isolated fluid impingement and secondary flow patterns may play a major role in the initiation of side-wall aneurysm initiation. We are unable to determine if this role is through direct or indirect mechanisms but hypothesize that elevations in isolated fluid impingement mark areas of cerebral vasculature that are at risk for aneurysm initiation. Thus, this indicator provides vascular locations to focus future study of side-wall aneurysm initiation.